PILOT STUDI: MANAJEMEN DIRI PASIEN DIABETES MELITUS DI RUMAH SAKIT HL. MANAMBAI ABDULKADIR: Pilot study: Self-Management Among Diabetes Mellitus Patients at HL. Manambai Abdulkadir Hospital - satriya pranata (LPPM STIKES Pemkab Jombang, 2019)
Background: The population of people with diabetes mellitus is increasing every year, furthermore included into number three of deadliest disease in Indonesia. The total number of patients with diabetes mellitus currently are 10.3 million, predicted in 2045, the population will increase to 16.7 million. The main cause population of people with diabetes mellitus are increasing due to public awareness regarding self-management is still less. No researcher has been conducted research about diabetes self-management in HL. Manambai Abdulkadir hospitals. Objectives of the Pilot Study: the main objective in this pilot study was to understand the self-management of people with diabetes mellitus in HL Manambai Abdulkadir hospitals. Methodology: The participants in this pilot study were people diabetes mellitus type 2 in HL Manambai Abdulkadir hospitals using cross sectional design by diabetes self-management, self-efficacy, diabetes self-management knowledge and diabetes distress scale questionnaire. Results: 60% of patients in HL Manambai Abdulkadir hospitals had lack of self-management. The result from measuring of distress scale, knowledge and self-efficacy of patients are related to self-management of patients with diabetes mellitus with P Value <0.05. Conclusion: further research is needed with additional interventions to overcome the lack of self-management to people who suffer diabetes mellitus in HL Manambai Abdulkadir Hospital.